An Electronically Controllable Voltage-Mode MOSFET-Only Single-Input Dual-Output Filter - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2019)
A new design of voltage mode (VM), single-input dual-output MOSFET-only filter which has electronic tunability property is presented without using passive circuit elements like resistors and capacitors. The filter topology is able to realize low-pass (LP) and band-pass (BP) filter functions with using the same circuit configuration. The proposed filter is laid-out in the Cadence environment using 0.18-mu m TSMC CMOS technology parameters. The layout area is only 344.4 mu m(2) and the power consumption is about 170 mu W. Furthermore, variations in the center frequency of the BP filter are presented performing Monte Carlo (MC) analysis to reinforce the filter results. Also, the noise performance of the proposed filter is investigated and it is shown that the theoretical and simulation results are in very good agreement.
Keywords: Voltage mode; MOSFET only electronically controllable; CMOS REALIZATION; MULTIFUNCTION FILTER; AMPLIFIER; DESIGN